Case Report: Gonio-endoscopy: a novel approach to minimally invasive glaucoma surgery in a glaucomatous eye - Matsushita, Kenji; Kawashima, Rumi; Kanazawa, Noriaki; Usui, Shinichi; Nishida, Kohji (Frontiers in Ophthalmology, 2023)
The gonio-endoscope is a novel device for use during minimally invasive glaucoma surgery (MIGS) to treat glaucomatous eyes with cloudy cornea. The MIGS procedure requires a surgical gonioprism lens for direct visualization of the angle, intraoperative manipulation of the surgical microscope and the patient's head position, and the patient's eye without a cloudy cornea. In cases with cloudy corneas or limitation of neck movement, MIGS cannot be safely performed.Gonio-endoscopy facilitates clear visualization of the trabecular meshwork (TM) to perform MIGS safely and easily even in a patient with corneal opacities or limitation of neck movement with no additional MIGS procedures. We report the first case in which we performed the newly developed a 10,000-pixel high-resolution 23-gauge gonio-endoscopic operation.The patient was a 58-year-old man with Down syndrome who had secondary glaucoma bilaterally after cataract surgery and long-time use of a steroid for atopic dermatitis and allergic conjunctivitis. His left eye had a cloudy cornea after penetrating keratoplasty for keratoconus with severe corneal residual scarring after prior resolved corneal hydrops. When the intraocular pressure (IOP) in his left eye increased to 41 mmHg despite the maximum use of anti-glaucoma eyedrops, he was referred to our hospital. Anterior-segment optical coherence tomography showed an open angle. We developed a new gonio-endoscope (MACHIDA Endoscope Co., Ltd., Chiba, Japan and NIPRO CORPORATION, Osaka, Japan), the probe of which is bent appropriately to aid visualization of and access to the TM. After obtaining clinical approval from the government and our institution, we could safely perform a high-resolution 23-gauge gonio-endoscopy-assisted microhook ab interno trabeculotomy (μLOT). The IOP decreased to 10 mmHg and the visual acuity has been preserved with no major complications for 1 year postoperatively.Conclusions: This new technique of clear gonio-visualization using a gonio-endoscope might be helpful for a safe and easy μLOT in patients with cloudy corneas. This device can apply to other types of MIGS procedures and cases with pathological diagnoses of glaucoma that are difficult to treat.